1966
DOI: 10.1084/jem.123.1.33
|View full text |Cite
|
Sign up to set email alerts
|

The REACTION MECHANISM OF SS1C-Globulin (C'3) IN IMMUNE HEMOLYSIS

Abstract: In addition to being part of the classical third component of complement, /31c-globulin (1) has been shown to play a key role in the mechanism of immune adherence (2), conglutination, immune conglutination (3), and erythrophagocytosis in vitro (4) and in vivo (5).Since the various functions of/3m-globtflin appear to depend upon attachment of the protein to the erythrocyte surface, a study was carried out with the aim (a) to delineate the mechanism of transfer of file-globulin from the fluid phase to cell membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

1967
1967
1977
1977

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(76 citation statements)
references
References 20 publications
5
71
0
Order By: Relevance
“…This finding confirms the observation that labeling with radioactive iodine does not alter the complement activity of C'3 (21). Preparation of labeled C'3,.…”
Section: Introductionsupporting
confidence: 77%
“…This finding confirms the observation that labeling with radioactive iodine does not alter the complement activity of C'3 (21). Preparation of labeled C'3,.…”
Section: Introductionsupporting
confidence: 77%
“…The roles of P1c deposition and of diminished synthesis in keeping concentrations low cannot be defined by the present study. 1 The present observations coincide with the investigations of Muller-Eberhard and associates (6), who used radiolabeled /81c in detailed studies 1 In vivo breakdown of jic and persistence of breakdown products in the circulation could introduce error in the isotopic measurement of pic disappearance. If the portion of the molecule that yielded alpha2D were isotopically labeled, the breakdown product would contribute counts and the half-life calculated for jc would be erroneously long.…”
supporting
confidence: 73%
“…In vitro studies of the reaction mechanism of C'3 in immune hemolysis have shown that only 5-10% of the available C'3 attaches to red blood cells or antigen-antibody complexes. The remainder (90-95%) of whole serum C'3 is converted to C'3i (21). It appears likely that during in vivo complement activation C'3 is converted to C'3i in the plasma or extravascular spaces, and only a small proportion of the C'3 is fixed to tissues.…”
Section: Resultsmentioning
confidence: 99%